2016
DOI: 10.4317/medoral.21182
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Progesterone hormone receptor expression in oral cavity cancer

Abstract: BackgroundRecent studies have shown an increase in the incidence of oral squamous cell carcinoma (OSCC) in younger patients. The hypothesis that tumors could be hormonally induced during pregnancy or in young female patients without the well-known risk factors alcohol or tobacco abuse seems to be plausible.Material and MethodsEstrogen Receptor alpha (ERα) and Progesterone Receptor (PR) expression were analyzed in normal oral mucosa (n=5), oral precursor lesions (simple hyperplasia, n=11; squamous intraepitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
2
20
1
3
Order By: Relevance
“…To our knowledge, this is the first report of ERa expression being associated with improved outcomes in a head and neck cancer population. Despite extensive study in cervical and breast cancer (9,27,31,32,(38)(39)(40)(41), ERa has received little attention in head and neck cancer (30,(42)(43)(44)(45)(46)(47)(48). Early studies failed to identify clinically significant quantities of estrogen receptor in HNSC (42), perhaps because those studies predated the increased incidence of HPV-positive disease, which we have shown is highly related to ERa expression.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, this is the first report of ERa expression being associated with improved outcomes in a head and neck cancer population. Despite extensive study in cervical and breast cancer (9,27,31,32,(38)(39)(40)(41), ERa has received little attention in head and neck cancer (30,(42)(43)(44)(45)(46)(47)(48). Early studies failed to identify clinically significant quantities of estrogen receptor in HNSC (42), perhaps because those studies predated the increased incidence of HPV-positive disease, which we have shown is highly related to ERa expression.…”
Section: Discussionmentioning
confidence: 92%
“…Early studies failed to identify clinically significant quantities of estrogen receptor in HNSC (42), perhaps because those studies predated the increased incidence of HPV-positive disease, which we have shown is highly related to ERa expression. Although ERa has been identified previously in HNSC specimens with a wide range of reported incidence [10%-76% in laryngeal cancer (44)(45)(46); 11%-50% in oral cavity cancer (43,47,48)], it has not been described as a biomarker for HNSC outcomes (30,43).…”
Section: Discussionmentioning
confidence: 99%
“…PRs in head and neck epithelial cells (with the exception of melanomas). Grimm et al, 37 in their in vivo survey, detected positive ER expression in 5/46 (11%) OSCC specimens, but the 5 ER-positive OSCC samples were all from older male patients, whereas all young female patients were negative for ER and PR.…”
Section: Discussionmentioning
confidence: 94%
“…15 Alternatively, different authors have hypothesized that the rapid growth of an OSCC in pregnancy could be induced by altered expression of ERs and PRs, although controversial results have been reported regarding this possibility. 15,20,[37][38][39] Chang et al 38 and Lukits et al 39 reported that 43% and 50% of studied OSCCs, respectively, exhibited the presence of ERs in human tongue OSCC cell lines. In contrast, Atabo and Bradley 15 reported the total absence of ERs or Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, 27% of the tumors expressed PR. A study by Grimm et al [37] found no expression of PR Fig. 1 Immunohistochemical staining pattern of AR, PR, and ERbeta receptors in oropharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 98%